2014
DOI: 10.1111/evo.12541
|View full text |Cite
|
Sign up to set email alerts
|

Cold adaptation shapes the robustness of metabolic networks inDrosophila melanogaster

Abstract: When ectotherms are exposed to low temperatures, they enter a cold-induced coma (chill coma) that prevents resource acquisition, mating, oviposition, and escape from predation. There is substantial variation in time taken to recover from chill coma both within and among species, and this variation is correlated with habitat temperatures such that insects from cold environments recover more quickly. This suggests an adaptive response, but the mechanisms underlying variation in recovery times are unknown, making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 85 publications
4
63
1
Order By: Relevance
“…Similarly complex perturbation of metabolic pathways and metabolomic composition was also documented in response to a change of temperature (Williams et al, 2014). Such complexity complicates interpretation of the results.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly complex perturbation of metabolic pathways and metabolomic composition was also documented in response to a change of temperature (Williams et al, 2014). Such complexity complicates interpretation of the results.…”
Section: Discussionmentioning
confidence: 90%
“…Chill coma recovery time has a genetic basis and responds to climatic selection, showing latitudinal clines on multiple continents whereby insects from colder regions recover more quickly [10,11], and a robust response to artificial selection [12][13][14]. Chill coma onset occurs due to failure of the neuromuscular system, and ionic and osmotic homoeostasis are progressively lost during low-temperature exposure [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila equinoxialis and D. melanogaster showed smaller but qualitatively similar responses with the addition of an increase in the possible purine. Increases in maltose levels have previously been found in response to cold shock treatments in D. melanogaster (Overgaard et al, 2007;Pedersen et al, 2008) and maltose has also been found to increase in D. melanogaster selected for high chill susceptibility (Williams et al, 2014). Maltose has been linked to the protection and function of proteins and membranes during temperature stress (Kaplan and Guy, 2004;Pereira and Hünenberger, 2006), and maltose accumulation has been linked to a stress-induced increase in amylase activity in plants ( Kaplan and Guy, 2004).…”
Section: Metabolite Response To Cold Exposurementioning
confidence: 94%
“…The relatively small response to cold exposure suggests that these species maintain their metabolite homeostasis far better than the chill-susceptible species. Similarly, the metabolomes of cold-selected, cold-acclimated and rapidly cold-hardened D. melanogaster are less responsive to cold exposure than warm-acclimated flies or flies directly exposed to a cold shock (Overgaard et al, 2007;Colinet et al, 2012;Williams et al, 2014). The increases in trehalose and the possible purine found in response to cold in D. persimilis and D. montana seem to be adaptive for coping with the cold stress.…”
Section: Metabolite Response To Cold Exposurementioning
confidence: 99%